Role of microRNA-34a in blood–brain barrier permeability and mitochondrial function in ischemic stroke - Payne, Cole T.; Tabassum, Sidra; Wu, Silin; Hu, Heng; Gusdon, Aaron M.; Choi, Huimahn A.; Ren, Xuefang S. (Frontiers in Cellular Neuroscience, 2023)
Over the past decade, there has been an uptick in the number of studies conducting research on the role of microRNA (miRNA) molecules in stroke. Among these molecules, miR-34a has emerged as a significant player, as its levels have been observed to exhibit a substantial rise following ischemic events. Elevated levels of miR-34a have been found to have multiple effects, including the modulation of inflammatory molecules involved in the post-stroke recovery process, as well as negative effects on the blood-brain barrier (BBB) permeability. Interestingly, the increase of miR-34a appears to increase BBB permeability post stroke, through the negative effect on mitochondrial function. The strength of mitochondrial function is crucial for limiting para-cellular permeability and maintaining the structural integrity of the BBB. Furthermore, the activation of ischemic repair mechanisms and the reduction of ischemic event damage depend on healthy mitochondrial activity. This review aims to emphasize the involvement of miR-34a in ischemic stroke, specifically its interaction with mitochondrial genes in cerebrovascular endothelial cells, the effect on mitochondrial function, and lastly its regulatory role in BBB permeability. A comprehensive understanding of the role of miR-34a in maintaining BBB integrity and its contribution to the pathogenesis of stroke holds significant value in establishing a foundation for the development of future therapeutics and diagnostic markers.